Future projections of biodiversity and ecosystem services in Europe with two integrated assessment models - Veerkamp, Clara J.; Dunford, Robert W.; Harrison, Paula A.; Mandryk, Maryia; Priess, Jörg A.; Schipper, Aafke M.; Stehfest, Elke; Alkemade, Rob (Regional Environmental Change, 2020)
Projections of future changes in biodiversity and ecosystem services (BES) are of increasing importance to inform policy and decision-making on options for conservation and sustainable use of BES. Scenario-based modelling is a powerful tool to assess these future changes. This study assesses the consequences for BES in Europe under four socio-environmental scenarios designed from a BES perspective. We evaluated these scenarios using two integrated assessment models (IMAGE-GLOBIO and CLIMSAVE IAP, respectively). Our results showed that (i) climate and land use change will continue to pose significant threats to biodiversity and some ecosystem services, even in the most optimistic scenario; (ii) none of the four scenarios achieved overall preservation of BES in Europe; and (iii) targeted policies (e.g. on climate change, biodiversity conservation and sustainable land management) and behavioural change (e.g. reducing meat consumption, water-saving behaviour) reduced the magnitude of BES loss. These findings stress the necessity of more ambitious policies and actions if BES in Europe are to be safeguarded. We further found that the multi-modelling approach was critical to account for complementary BES dimensions and highlighted different sources of uncertainties (e.g. related to land use allocation, driving forces behind BES changes, trade assumptions), which facilitated nuanced and contextualised insights with respect to possible BES futures.